2013
DOI: 10.1109/tac.2012.2218150
|View full text |Cite
|
Sign up to set email alerts
|

Semidefinite Hankel-Type Model Reduction Based on Frequency Response Matching

Abstract: This paper is dedicated to model order reduction of linear time-invariant systems. The main contribution of this paper is the derivation of two scalable stability-preserving model reduction algorithms. Both algorithms constitute a development of a recently proposed model reduction method. The algorithms perform a curve fitting procedure using frequency response samples of a model and semidefinite programming methods. Computation of these samples can be done efficiently even for large scale models.Both algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Besides, in the past few decades, many methods have been introduced for solving the problem of model reduction such as Hankel norm based methods [39], [40], H ∞ norm based methods [41], [42], H 2 norm based methods [43], and H 2 -H ∞ based methods [44]. In addition, some other methods such as balanced truncation approach [45], [46] and frequency response matching [47] have also been proposed. For model reduction of type-1 FMB systems, there have been some research results reported in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in the past few decades, many methods have been introduced for solving the problem of model reduction such as Hankel norm based methods [39], [40], H ∞ norm based methods [41], [42], H 2 norm based methods [43], and H 2 -H ∞ based methods [44]. In addition, some other methods such as balanced truncation approach [45], [46] and frequency response matching [47] have also been proposed. For model reduction of type-1 FMB systems, there have been some research results reported in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mathematical modeling of physical systems often results in high‐order models and it is desirable to replace these high‐order models with reduced ones with respect to some given criteria. This has motivated the study of the model reduction problem with various approaches . For the model reduction problems of MJLS, the efforts are mainly concentrated on three kinds of reduction problems, namely, classical balanced truncation model reduction, H ∞ model reduction, and H 2 model reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, the issue of model reduction has been paid considerable attention. There are an army of efficient approaches to settle the difficulty of model reduction, such as the optimal H 2 approach [19], the H ∞ approach [14], [18], the L 2 -L ∞ approach [6] and the optimal Hankel-norm approach [13]. The model reduction problem with a Hankelnorm sense has been investigated by numerous researchers.…”
Section: Introductionmentioning
confidence: 99%